2005
DOI: 10.1523/jneurosci.2112-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Cholinergic Receptors in the Rat Cerebellum: Multiple Heteromeric Subtypes

Abstract: . The subtypes of nAChRs in the cerebellum are not known in any detail, except that, in addition to the homomeric ␣7 subtype, there appears to be one or more heteromeric subtypes consisting of combinations of ␣ and ␤ subunits. To begin to better understand the potential roles of these heteromeric nAChRs in cerebellar circuitry and their potential as targets for nicotinic drugs, we investigated their subunit composition. Using subunit-selective antibodies in sequential immunoprecipitation assays, we detected si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 44 publications
5
75
0
Order By: Relevance
“…2), and consequently the VD Tot for 2-[ 18 F]F-A-85380 in cerebellum was more than twice as large as the VD ND determined for any of the brain regions studied (Table 3). This result is consistent with the presence of nAChRs in the rat cerebellum, which was established more than 15 years ago (Clarke et al, 1985;Flores et al, 1992), and with the recent in vitro characterization of the α4β2* subtype in this brain region (Turner and Kellar, 2005). The obvious problem in computing BP* for 2-[ 18 F]F-A-85380 in the rat using the cerebellum as a reference region will be a serious underestimation (ca.…”
Section: Reference Region Methods Considerations For 2-[ 18 F]f-a-85380supporting
confidence: 90%
“…2), and consequently the VD Tot for 2-[ 18 F]F-A-85380 in cerebellum was more than twice as large as the VD ND determined for any of the brain regions studied (Table 3). This result is consistent with the presence of nAChRs in the rat cerebellum, which was established more than 15 years ago (Clarke et al, 1985;Flores et al, 1992), and with the recent in vitro characterization of the α4β2* subtype in this brain region (Turner and Kellar, 2005). The obvious problem in computing BP* for 2-[ 18 F]F-A-85380 in the rat using the cerebellum as a reference region will be a serious underestimation (ca.…”
Section: Reference Region Methods Considerations For 2-[ 18 F]f-a-85380supporting
confidence: 90%
“…␣4␤2* nAChRs are the most abundant nAChR subtypes in the mammalian brain, accounting for 90% of high affinity nAChRs (44). They assemble with additional subunits in vivo and form more complex ␣4␤2* subtypes, including but not limited to ␣4␤2␣2*, ␣4␤2␣3*, ␣4␤2␣6*, and ␣4␤2␤4 (37,45,46). These nAChRs could form one accessory ␣/␣4 agonist site and two identical or different ␣/␤ agonist sites, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in the Section 'Pharmacological properties of neuronal nAChRs and their involvement in human disorders', b4-expression in the VTA is low, but b4-containing receptors are found in the habenula, locus coeruleus, IPN and cerebellum. 58,71,173 a3b4* have lower-binding affinity than do a4b2* receptors in transfected cells, 174 they do not become fully occupied and saturated at the nicotine concentration range detected in smokers' plasma during the day, 16 and are more resistant to rapid desensitization than are a4b2* receptors. 175 Taking receptor affinity, saturation and differential desensitization considerations into account, Rose 16 suggested that b4-subunit containing receptors contribute to the reinforcing effect of nicotine.…”
Section: General Overviewmentioning
confidence: 99%
“…In addition, a3-containing nAChRs are found in several regions of rodent brain, including the VTA, pineal gland, medial habenula, IPN, brainstem nuclei, hippocampus and cerebellum. [56][57][58] CHRNA5. In humans, mRNA encoding the a5-nicotinic subunit has been detected in several structures of the nervous system (including cortex) but appears to be mainly expressed in the cerebellum and thalamus (where it assembles with a4b2* and a3b2* receptor subtypes) and the autonomic ganglia.…”
Section: Neuronal Nachrs Nachr Subunitsmentioning
confidence: 99%